2015
DOI: 10.4067/s0718-95162015005000019
|View full text |Cite
|
Sign up to set email alerts
|

ACC-deaminase and/or nitrogen fixing rhizobacteria and growth of wheat (Triticum Aestivum L.)

Abstract: Plant growth promoting rhizobacteria (PGPR) are beneficial bacteria, which can enhance the growth of the plants, when applied to crops. A pot experiment was conducted to examine the effect of six PGPR isolates on the growth of wheat. Inoculation with rhizobacterial isolates increased the all measured physical, chemical and enzymatic growth parameters compared to control (CK). However, the WAN1 isolate had the highest effect, and significantly (P < 0.05) increased the root length (3.51-fold), shoot length (3.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…It seems that a mixture of the above mentioned mechanisms in T5 strain treatment has been the most efficient on plant height, root and shoot dry weight of canola seedlings under salinity stress. Hassan et al (2015) reported similar results.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It seems that a mixture of the above mentioned mechanisms in T5 strain treatment has been the most efficient on plant height, root and shoot dry weight of canola seedlings under salinity stress. Hassan et al (2015) reported similar results.…”
Section: Discussionsupporting
confidence: 63%
“…In our study, T5 and T4 treatments were the best rhizobacterial isolates due to having combination of plant growth promoting activities. Similarly, Hassan et al (2015) reported that the isolates having both ACC-deaminase activity and nitrogen fixing ability (i.e., WAN1) were more efficient isolates than those of having nitrogen fixing activity or ACC-deaminase activity alone. In our study, only the ACC-deaminase producing strains (T3, T4 and T5) showed significant increase in chlorophyll content compared to the control (Figure 1-C).…”
Section: Discussionmentioning
confidence: 90%
“…This partly confirms the findings of Fageria and Moreira (2011), who claim that increasing nutrient supplies in the soil may decrease root length, but increase root weight. In laboratory conditions, Hassan et al (2015) indicated that rhizobacterial isolates increased all measured physical, chemical and enzymatic growth parameters of wheat. Rhizobacteria increased root length, shoot length, dry weight, N uptake by shoots and by roots.…”
Section: Discussionmentioning
confidence: 98%
“…The use of microorganisms is important for sustainable agriculture and plant growth, as they increase the availability and absorption of nutrients, reducing dependence on chemical fertilizers that destabilize agroecosystems (Banerjee et al, 2017;Hassan et al, 2015).…”
Section: Soil Analysismentioning
confidence: 99%